Novel Genetic Variants of Sporadic Atrial Septal Defect (ASD) in a Chinese Population Identified by Whole-Exome Sequencing (WES) - Liu, Yong; Cao, Yu; Li, Yaxiong; Lei, Dongyun; Li, Lin; Hou, Zong Liu; Han, Shen; Meng, Mingyao; Shi, Jianlin; Zhang, Yayong; Wang, Yi; Niu, Zhaoyi; et al. (Medical science monitor, 2018)
BACKGROUND Recently, mutations in several genes have been described to be associated with sporadic ASD, but some genetic variants remain to be identified. The aim of this study was to use whole-exome sequencing (WES) combined with bioinformatics analysis to identify novel genetic variants in cases of sporadic congenital ASD, followed by validation by Sanger sequencing. MATERIAL AND METHODS Five Han patients with secundum ASD were recruited, and their tissue samples were analyzed by WES, followed by verification by Sanger sequencing of tissue and blood samples. Further evaluation using blood samples included 452 additional patients with sporadic secundum ASD (212 male and 240 female patients) and 519 healthy subjects (252 male and 267 female subjects) for further verification by a multiplexed MassARRAY system. Bioinformatic analyses were performed to identify novel genetic variants associated with sporadic ASD. RESULTS From five patients with sporadic ASD, a total of 181,762 genomic variants in 33 exon loci, validated by Sanger sequencing, were selected and underwent MassARRAY analysis in 452 patients with ASD and 519 healthy subjects. Three loci with high mutation frequencies, the 138665410 FOXL2 gene variant, the 23862952 MYH6 gene variant, and the 71098693 HYDIN gene variant were found to be significantly associated with sporadic ASD (P<0.05); variants in FOXL2 and MYH6 were found in patients with isolated, sporadic ASD (P<5×10^-4). CONCLUSIONS This was the first study that demonstrated variants in FOXL2 and HYDIN associated with sporadic ASD, and supported the use of WES and bioinformatics analysis to identify disease-associated mutations.